Decolorization Of Remazol Brilliant Violet 5r And Procion Red Mx-5b By Trichoderma Species - Vanessa Jane Zainip; Liyana Amalina Adna; Mohamed Soliman Elshikh (Tecno Scientifica, 2024)
Volume: 1 Issue: 2 (page: 108-117)